MON-344 Uncommon Etiology of Hypophosphatemia and Secondary Hyperparathyroidism: Ferric Carboxymaltose Infusion - Sever, Sakine (J Endocr Soc, 2020)
Background: Hypophosphatemia has been recognized as one of the side effect of intravenous ferric carboxymaltose infusion. This effect is thought to be secondary to fibroblast growth factor 23 (FGF 23) mediated renal phosphate wasting and associated with calcitriol deficiency and secondary hyperparathyroidism. Clinical Case: A 76 years old male patient with medical problems including hypertension, type 2 diabetes mellitus, hyperlipidemia, paroxysmal atrial fibrillation, nephrolithiasis, spinal stenosis and chronic anemia was referred to endocrinology clinic for osteoporosis management. Bone density scan showed left femur neck T-score of -2.5 and L1-L4 lumbar spine T-score of 1.4. He reported pain on back and bilateral posterior thighs, difficulty with ambulation which were partly attributed to severe spinal stenosis that he was planned to have surgery for. Muscle strength was normal on examination. Laboratory studies were obtained for osteoporosis work up and showed: Calcium: 8.9 mg/dL (8.8-10.2 mg/dL), Creatinine: 0.77 mg/dL (0.74-1.35 mg/dL), GFR: 88 mL/min/BSA, Albumin 4.5 g/dL (3.5-5.0 g/dL), 25-Hydroxy vitamin D: 26 ng/mL, Magnesium 1.8 mg/dL (1.7-2.3 mg/mL), 1,25 Dihydroxy Vitamin D 24 pg/mL (18-64 pg/mL), Phosphorus: 1 mg/dL (2.5-4.5 mg/dL), PTH 163 pg/mL (15-65 pg/mL), Hemoglobin 12.9 mg/dL (13.2-16.6 mg/dL). Due to hypophosphatemia tumor induced osteomalacia diagnosis was entertained and further work up was considered in this regard however later noted that patient received ferric carboxymaltose 750 mg infusion two times within last 3 weeks for iron deficiency anemia. Hemoglobin level was 8.6 mg/dL before the infusions. After oral phosphate replacement the phosphate level improved to 2.4 mg/dL. Serum FGF 23 level was measured and it was normal at 108 RU/mL (<180 RU/mL). He was then started on bisphosphonate treatment for osteoporosis. Conclusion: Hypophosphatemia and secondary hyperparathyroidism can be seen after ferric carboxymaltose infusion due to FGF-23 mediated mechanism. In literature various presentations were reported from transient- asymptomatic hypophosphatemia to severe acute symptomatic hypophosphatemia along with persistent hypophosphatemia with osteomalacia and fragility fractures due to recurrent ferric carboxymaltose infusions. Thus, one should keep this possible side effect in mind during evaluation of hypophosphatemia and osteoporosis. References: 1. Wolf M, Chertow GM, Macdougall IC, Kaper R, Krop J, Strauss W. Randomized trial of intravenous iron-induced hypophosphatemia. JCI Insight. Dec 6 2018;3(23):e124486 2. Fang W, McMahon LP, Bloom S, Garg M. Symptomatic severe hypophosphatemia after intravenous ferric carboxymaltose. JGH Open. October 2019, volume 3, issue 5, P 438-440